MicroRNA‐containing extracellular vesicles released from endothelial colony‐forming cells modulate angiogenesis during ischaemic retinopathy. Issue 12 (20th June 2017) - Dellett, Margaret; Brown, Eoin D.; Guduric‐Fuchs, Jasenka; O'Connor, Anna; Stitt, Alan W.; Medina, Reinhold J.; Simpson, David A.
Abstract: Endothelial colony‐forming cells (ECFCs) are a defined subtype of endothelial progenitors that modulate vascular repair and promote perfusion in ischaemic tissues. Their paracrine activity on resident vasculature is ill‐defined, but mediated, at least in part, by the transfer of extracellular vesicles (EVs). To evaluate the potential of isolated EVs to provide an alternative to cell‐based therapies, we first performed a physical and molecular characterization of those released by ECFCs. Their effects upon endothelial cells in vitro and angiogenesis in vivo in a model of proliferative retinopathy were assessed. The EVs expressed typical markers CD9 and CD63 and formed a heterogeneous population ranging in size from ~60 to 1500 nm by electron microscopy. ECFC EVs were taken up by endothelial cells and increased cell migration. This was reflected by microarray analyses which showed significant changes in expression of genes associated with angiogenesis. Sequencing of small RNAs in ECFCs and their EVs showed that multiple microRNAs are highly expressed and concentrated in EVs. The functional categories significantly enriched for the predicted target genes of these microRNAs included angiogenesis. Intravitreally delivered ECFC EVs were associated with the vasculature and significantly reduced the avascular area in a mouse oxygen‐induced retinopathy model. Our findings confirm the potential of isolated EVs to influence endothelial cell function and act as a therapy to modulate angiogenesis. The functions associated with the specific microRNAs detected in ECFC EVs support a role for microRNA transfer in mediating the observed effects.